2020
DOI: 10.1108/ejmbe-09-2018-0100
|View full text |Cite
|
Sign up to set email alerts
|

Bank performance variability and strands of inflationary conditions

Abstract: PurposeThis study seeks to examine the extent to which strands of inflationary related conditions (inflation expectations, inflation uncertainty and realized inflation); macroeconomic uncertainty and the likelihood of recessionary conditions influence performance indicators in the US banking sector over a specified time period.Design/methodology/approachThe study adopts seemingly unrelated regression model (SUR) advanced by Zellner (1962) in its examination of how specific strands of inflationary conditions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…GARCH process employed in this study takes a cue from notable research studies that used the procedure in respective studies and have confirmed its effectiveness. These works include Abaidoo and Agyapong (2021), Abaidoo and Anyigba (2020), Gö kbulut and Pekkaya (2014) and Asteriou and Price (2005), to mention but a few. GARCH is a statistical model for analyzing time series data in which the variance of the error term is serially autocorrelated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GARCH process employed in this study takes a cue from notable research studies that used the procedure in respective studies and have confirmed its effectiveness. These works include Abaidoo and Agyapong (2021), Abaidoo and Anyigba (2020), Gö kbulut and Pekkaya (2014) and Asteriou and Price (2005), to mention but a few. GARCH is a statistical model for analyzing time series data in which the variance of the error term is serially autocorrelated.…”
Section: Methodsmentioning
confidence: 99%
“…The process theorizes that the derivative of the lags of a variable denote its conditional variance; the variance of the stochastic term therefore captures the uncertainty data from the base variable. According to Abaidoo and Anyigba (2020), the GARCH framework captures fluctuations or volatility associated with a base variable as a measure of instability associated with the variable. The GARCH (1,1) equation used in deriving the data for macroeconomic uncertainty and inflation uncertainty variables is presented below.…”
Section: Methodsmentioning
confidence: 99%
“…We adopt this approach in deriving the volatility data as against other approaches including using the standard deviation because volatility in price of such key commodities presents a state of uncertainty that could affect key sectors of an economic setting including the returns on the stock exchange. This approach is adopted following its application by notable research works including Abaidoo and Kwenin (2013), Gokbulut and Pekkaya (2014), and Abaidoo and Anyigba (2020). This model is presented in equation () below.…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…It is worth emphasizing that this approach has been used extensively in the literature by various authors. Mention could be made of such studies, including Asteriou and Price (2005), Akgul and Sayyan ( 2005), Fountas and Karanasos (2007) and Abaidoo and Anyigba (2020), among others, that have resorted to employing GARCH to derive volatility data. In GARCH modelling, the conditional variance depends on its own lags.…”
Section: Deriving Volatility Variablesmentioning
confidence: 99%